THE RESULTS AND PROSPECTS OF INTRODUCTIVE TESTING OF REPRESENTATIVES OF TAXODIACEAE F. W. NEGER FAMILY IN THE BOTANICAL GARDEN OF NATIONAL UNIVERSITY OF LIFE AND ENVIRONMENTAL SCIENCES OF UKRAINE - Slusar, S. I.; Maievskyi, K. V. (Forestry and Forest Melioration, 2018)
Introduction The results of species’ introduction of the family Taxodiaceae F. W. Neger in open ground were analyzed, potential capabilities of plants introductive testing at the level of species complexes Metasequoia glyptostroboides Hu et Cheng, Taxodium distichum (L.) Rich., Cryptomeria japonica D. Don were identified. Materials and Methods The researches were carried out in the 1996-2015 in Botanical Garden of National University of Life and Environmental Sciences of Ukraine (NULES of Ukraine), Kyiv. Species and cultivars of family Taxodiaceae were the research objects. For the selection of perspective for the further introduction species we used O.A. Kalinichenko’s methodological approaches (1978), based on determining of adaptation success and introduction practicability (i.e. indicators of environmental sustainability, viability and utilitarian properties). Results and Conclusions The used technologies allow reproducing the most stable and promising (for the wide introduction) world famous decorative cultivars (those species that are valuable for the further introductive work). Analysis of world famous decorative cultivars’ assortment of Taxodiaceae species confirms that only a small portion was tested in Ukraine. To improve the situation it is necessary, in particular, to carry out continuous monitoring of global and national markets of ornamental plants for the selection, testing and use in Ukraine the most promising forms. High environmental stability, the absence of pests and diseases, availability of good-quality seeds and decorativeness indicate the possibility of widespread using of individuals of the family Taxodiaceae in landscaping. Their insufficient distribution can be explained only by the lack of these plants in an assortment of national ornamental nurseries. The main reason for this is certain difficulties in the vegetative reproduction of plants and impossibility of obtaining a sufficient amount of planting material. To solve the problem it is necessary to enrich dendrological collections with new cultivars, to conduct introductive testing, to create stool plantations for seed and vegetative reproduction of the most stable and economically valuable plants. The technologies used in the Botanical Garden allow reproducing the most stable and promising for the widespread introduction world famous ornamental cultivars (of those species primary test results of which are satisfactory, that is, valuable for the further introductive work). The largest volume of information on the availability of cultivars in the world is given by the UK Royal Horticultural Society, founded in 1804. It is the leading cultivar registration authority. Under the conditions of the Botanical Garden of NULES of Ukraine two species of family Taxodiaceae are promising for the further introduction: metasequoia, which plants are the most adapted (III level of adaptation), double-row taxodium (ІІ level of adaptation). These types should be used in forestry, forest reclamation and landscaping. Because once primary introduction of individual plants of Japanese cedar was carried out the results of its primary testing cannot be the final ones. Therefore, it is advisable to conduct re-introduction of these species from different points of the natural habitat, as well as to sow its local reproduction seeds.